Mengukir Sejarah Baru dalam Perayaan 1 Muharram di Desa Simpang Tiga - Hanifah, Fitriatul; Selpiana, Nur Azizah (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2025)
This article discusses the implementation of the IAIN SAS BABEL Real Work Lecture (KKN) program in Simpang Tiga Village as a form of community service and learning for students. Simpang Tiga Village, located in Simpang Renggiang District, East Belitung Regency, is a village with the majority of the population being Muslim. One of the main activities held is the 1 Muharram celebration which involves the local community in various religious and social activities. The novelty in this research lies in the reactivation of the previously inactive Mosque Youth Association (IRMAS), as well as the implementation of the 1 Muharram celebration for the first time in Simpang Tiga Village. This activity not only inspires people's religious insight, but also fosters religious traditions and strengthens relations between residents. This study used descriptive qualitative method. Data was collected through interviews, observation and documentation. Interviews were conducted with village officials and community members, observations were made of ongoing activities, and documentation included recording and taking pictures during the event. The main results of this research are the re-establishment of IRMAS with a new organizational structure, as well as the successful implementation of the 1 Muharram celebration. This event featured all village residents and involved various competitions such as the call to prayer, tartil, and a Muslim/Muslim fashion show. The closing event was marked by a torchlight parade which was attended by the village community. All of these activities show enthusiasm and active participation from the community, which creates a deep impression and is hoped to be continued by the younger generation in Simpang Tiga Village.